Metrics how to improve key business results - Klubeck, Martin (Apress, 2011)
Metrics are a hot topic. Executive leadership, boards of directors, management, and customers are all asking for data-based decisions. As a result, many managers, professionals, and change agents are asked to develop metrics, but have no clear idea of how to produce meaningful ones. Wouldn’t it be great to have a simple explanation of how to collect, analyze, report, and use measurements to improve your organization? Metrics: How to Improve Key Business Results provides that explanation and the tools you'll need to make your organization more effective. Not only does the book explain the “why” of metrics, but it walks you through a step-by-step process for creating a report card that provides a clear picture of organizational health and how well you satisfy customer needs. Metrics will help you to measure the right things, the right way—the first time. No wasted effort, no chasing data. The report card provides a simple tool for viewing the health of your organization, from the outside in. You will learn how to measure the key components of the report card and thereby improve real measures of business success, like repeat customers, customer loyalty, and word-of-mouth advertising. This book: (1) provides a step-by-step guide for building an organizational effectiveness report card, (2) takes you from identifying key services and products and using metrics, to determining business strategy, and (3) provides examples of how to identify, collect, analyze, and report metrics that will be immediately useful for improving all aspects of the enterprise, including IT.